Utilization Of Solar Power Plants (Plts) For Street Lighting As A Renewable Energy Solution On Gara Island, Batam - Gunawan Toto Hadiyanto; Jumadril JN; Kalbin Salim (CV. AFDIFAL MAJU BERKAH, 2026)
Limited electricity supply in rural areas results in suboptimal public street lighting. One environmentally friendly solution is the utilization of Solar Power Plants (PLTS). This study aims to analyze the potential use of PLTS as a power source for street lighting in rural regions. The methods employed include a literature review, measurement of solar irradiance, and simulation of the power requirements of LED lamps. The results indicate that a PLTS system consisting of a 100 Wp solar panel, a 12V/100Ah battery, and a 40W LED lamp is capable of providing illumination for approximately ±10 hours per night. The implementation of this system can reduce dependence on grid electricity and lower carbon emissions.